Применение быстрых нейтронов в лечении злокачественных новообразований головы и шеи - Грибова О. В. Ольга Вячеславовна; Мусабаева Л. И. Людмила Ивановна; Чойнзонов Е. Л. Евгений Лхамацыренович; Новиков В. А. Валерий Александрович; Лисин В. А. Валерий Андреевич (2015, 2015)
Заглавие с экрана